Morphology of the Utsjoki river valley and the uppermost shoreline on northernmost Finland - Mansikkaniemi, Hannu (Geographical Society of Finland, 1973)
The Utsjoki valley reaches strongly under the undulating fell plateau. The mean depth (Mh) and the mean width (Mw) have been determined in different parts of the valley. The mean depth is 110 m, varying from 80 to 210 m. The mean width varies from 0.6 to 2.0 km. As the width grows so the depth increases quite regularly. The shape of the valley is described using a width‑depth index (Mw/Mh). The valley is clearly narrowest in the lower part of the middle course where the index is 5‑6, and it is most open in the upper part of the middle course, 16‑21. In the cross‑section from of the valley there are six zones altogether. In the four uppermost zones the cross section is V‑shaped and U‑shaped in the two zones in the lower course. The thickness of fluvioglacial material at the bottom of the valley varies from 10 to 86 cm. A clear kame topography with water‑filled kettle holes is seen in the whole valley. The uppermost surface of the fluvioglacial material in the lower course is clearly levelled. Many kettle holes at lower levels are, however, quite fresh. The grain size of the fluvioglacial material varies considerably. Cobbles and small blocks are well rounded. Analyses of particles Ø 1–2 mm by graniformameter indicate that fine material is poorly rounded. A supposed shore line agreeing with the gradient of the Main postglacial shore line follows closely the uppermost levelled surfaces and washing limits in the lower course. It is evident that the water level in the lower course has been determined by the Main sea phase (P12). The effect of the sea has reached neither the middle course nor above it. Some dead ice blocks did not melt until the sea retreated. The uppermost sea phase of the Inari basin is about 500 years younger than sea phase in the Utsjoki river valley.